(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The Borghetto d’ Arroscia sequence begins with a little known basel post, followed by two lithostratigraphic Units: the M. Bignone Quartzites (Paleocene ? —Eocene ? ) and the Ubaga Limestones (Eocene). Three deformation phases affected the tectonic evolution of the Borghetto d’Arroscia element. They are shown by the minor structures (at outcrop scale) and by the major ones, surveyed at 1/10.000 scale. The first two phases are vergent outwards. The former (Fl ) is characterized by southvergent recumbent folds, the latter (Fl b) gives cut planes slightly dipping, forming the overthrust surface to the same direction. The third phase (F2) is retrovergent and does not change the general structural setting already reached.